Analisis Tarif Dan Setoran Bus Kobutri Jurusan KPAD — Antapani - Susilo, Budi Hartanto; Setia, Suhud; Himawan, Deni (Universitas Kristen Maranatha, 2005)
Currently, the Kobutri bus company operates only 8 units out of 12 units, and the route served is KPAD-Antapani. The level of service is relatively low as passengers are crammed standing like pindang fish. This may be due to the tariff charged to passengers is low so it does not cover the cost of operating the vehicle. Therefore, it is necessary to conduct research to determine the appropriateness of the applicable tariff. Data collection was carried out using a survey method to passengers, drivers, owners and managers to obtain primary and secondary data for the purposes of analyzing Vehicle Operating Costs (BOK), the amount of tariffs and actual real deposits Using the Cost Component Analysis Method, Determination of Tariffs and Deposits, and Net Present Value Analysis, appropriate values were obtained.From the results of the analysis, it was concluded that the tariffs and deposits obtained from the calculation of vehicle operating costs using the actual number of passengers were smaller than the tariffs set by the government. In this case, it means that the company gets enough profit and the amount of the existing tariff is not the main cause of the decline in Kobutri transportation services majoring in KPAD-Antapani.